Ecotourism and Art Mangunan Kaki Langit Tourism Village - Anwar Yahya, Fahmi; Khairune Nisa, An Nuur; Bahri, Iswan; Oktaviani Gustiarti, Putrisari (Ann Publisher, 2023)
Mangunan Kaki Langit Tourism Village is an ecotourism that focuses on community empowerment. The village was formed on March 9, 2014, by the Mangunan Dukuhan KKLPMD Organization. The name